Analisis Akuntabilitas dan Pengelolaan Keuangan Masjid Melalui Pendekatan Fenomenologi Studi Komparatif - Mardianton, Mardianton; Suwita, Hanifa; Sumarni, Ira; Efendi, Faisal (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This research aims to compare patterns of accountability and financial management of the Mosque through a comparative study phenomenological approach. Type of field research with a qualitative descriptive approach. The analysis technique uses comparative study phenomenology. The results of the study, Al-Mashun Grand Mosque and Medan Great Mosque have not fully implemented the accountability of their financial management, although they do not have a written SOP, but the implementation of management activities follows the laws and traditions of the previous mosque management. The Great Mosque's financial statements are audited by a public accountant every 2 months, while the Al-Mashun Grand Mosque's financial statements have never been audited, but the fairness of the report can be evaluated by Jama'ah exclusively. there is a separation of functions in the Mosque's cash expenditure which is kept in a bank account. The financial management of the Mosque has been transparent with the accessibility of the Mosque report by the Jama'ah.